Spsp2 hybrid carbon-supported Ru-Nx / C electrocatalyst rich in unsaturated coordination center as well as preparation method and application of spsp2 hybrid carbon-supported Ru-Nx / C electrocatalyst

By using sp&sp2 hybrid carbon solid-supported Ru-Nx/C electrocatalyst in the electrocatalyst, the problems of low ammonia yield and insufficient Faraday efficiency in the existing electrocatalytic nitrogen reduction synthesis ammonia are solved, and the nitrogen reduction synthesis ammonia at high efficiency and low potential is achieved, and the hydrogen evolution side reaction is inhibited.

CN119736657AActive Publication Date: 2025-04-01LIAONING UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411920688.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

In the existing electrocatalytic nitrogen reduction synthesis process, the ammonia yield is low, the Faraday efficiency is insufficient, and it is difficult to effectively inhibit the hydrogen evolution side reaction.

Method used

A Ru-Nx/C electrocatalyst rich in unsaturated coordination centers was designed and constructed. By using ruthenium complexes and hydrogen to replace graphyne aerogel as a precursor, the Ru-Nx catalytic active center was anchored on a three-dimensional carbon substrate with sp and sp2 hybrid carbons by Joule thermal heating.

Benefits of technology

It has achieved high efficiency nitrogen reduction in synthesis of ammonia at low potential, and the ammonia yield and Faraday efficiency have been significantly improved, which can be comparable to single-atom catalysts, while effectively inhibiting hydrogen evolution side reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736657A_ABST
    Figure CN119736657A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst materials, and particularly discloses a preparation method of spmp; the invention relates to an sp2 hybrid carbon immobilized Ru-Nx / C electrocatalyst rich in unsaturated coordination center and a preparation method and application thereof. The preparation method of the Ru-Nx / C electrocatalyst comprises the following steps: dissolving a ruthenium complex in methanol; and adding the hydrogen-substituted graphdiyne aerogel into the ruthenium complex solution for soaking, carrying out reduced pressure distillation, putting into a Joule heater, carbonizing in an argon atmosphere, and cooling to obtain Ru-Nx / C. The invention also discloses a preparation method of the Ru-Nx / C catalyst. Compared with graphene and other carbon material carriers, the catalyst has abundant sp hybrid carbon and defect sites, enhances the adsorption of nitrogen, and further improves the Ru-Nx / C electro-catalysis nitrogen reduction reaction activity. The catalyst has the advantages of being adjustable in catalytic microenvironment where active sites are located, high in substrate adsorption and activation capacity, simple in synthesis method, good in stability and the like, and a new material and a preparation method thereof are provided for efficient electrocatalytic nitrogen reduction synthesis of ammonia in a water phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalyst materials. 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst and its preparation method and its application in electrocatalytic synthesis of ammonia. Background Art

[0002] Ammonia is an important chemical that is widely used in chemicals, fertilizers, fuels, energy, etc., but its industrial production still relies on the traditional Haber-Bosch (HB) process, which consumes a large amount of fossil fuels and emits a large amount of carbon dioxide. Therefore, it is imperative to develop a new green and efficient process for synthesizing ammonia. Electrocatalytic nitrogen reduction synthesis of ammonia uses green electricity as the driving force and uses water as a proton source at room temperature and pressure to achieve the conversion from nitrogen to ammonia. This method does not use fossil energy, conforms to the concept of carbon neutrality, and is the most promising new method for synthesizing ammonia to replace the HB method.

[0003] So far, the ammonia yield of electrocatalytic nitrogen reduction to ammonia is generally 10-30 μg·h -1 mg -1 cat , the Faraday efficiency is between 10% and 20%, which is still a long way from industrial application. Designing and constructing efficient and stable electrocatalysts is the key and core to improving the performance of electrocatalytic ammonia synthesis, and it is also the only way to practicalize the electrocatalytic nitrogen reduction ammonia synthesis process. At present, among many metal-based catalysts, ruthenium (Ru) is the most promising nitrogen reduction electrocatalyst. However, how to improve its nitrogen reduction activity and effectively inhibit the hydrogen evolution side reaction is a difficult problem to be solved urgently. Based on this, we designed and constructed a composite catalyst containing an unsaturated coordination center Ru, a Ru-N x It has a strong adsorption effect on N2, which can effectively activate the N≡N triple bond and inhibit the occurrence of hydrogen evolution side reaction. 2 A new type of alkynyl carbon material with a highly π-conjugated system, hydrogen-substituted graphene aerogel, was used as a carbon precursor to convert Ru-N x The catalytic active center is anchored on a sp and sp 2 The sp and sp 2 The uneven charge distribution on the surface of the hybrid carbon substrate is also beneficial to regulating the electron cloud density of the catalytic active center, generating active sites in the interface area that are beneficial to the electrocatalytic nitrogen reduction synthesis of ammonia, further improving the catalytic activity.

[0004] Based on the above ideas, we selected ruthenium polypyridine complexes with different coordination numbers ([Ru(bpy)2]Cl2 and [Ru(bpy)3]Cl2) and hydrogen-substituted graphyne aerogel as precursors, and used Joule heating to carbonize Ru-N with adjustable unsaturated coordination centers. x Fixed to sp&sp 2 Highly efficient and stable Ru-N x / C composite electrocatalyst, achieving efficient nitrogen reduction to synthesize ammonia at a low potential of -0.1V (relative to the reversible hydrogen electrode). There are many types of ruthenium complexes, and the use of ruthenium complexes with different ligands can effectively adjust the Ru-N x / C, the type and content of N and other doped atoms, etc. Therefore, this method has good universality. Summary of the invention

[0005] In order to achieve the above-mentioned object, the present invention provides a method for preparing a highly efficient Ru-based electrocatalytic nitrogen reduction catalyst which is simple in method and easy to prepare on a large scale, and its application in nitrogen reduction synthesis of ammonia. x Precursor, hydrogen-substituted graphyne aerogel is the precursor of three-dimensional carbon carrier, and Ru-N with adjustable unsaturated coordination center is prepared by high temperature pyrolysis by Joule heating. x / C composite catalyst. Establish a method for preparing high-efficiency electrocatalytic materials and study their application in the field of electrocatalytic nitrogen reduction. x The catalytic activity of the Ru catalytic active center in / C is adjustable: the degree of unsaturated coordination and the catalytic microenvironment of the Ru catalytic active center can be adjusted by adjusting the coordination number of ruthenium in the ruthenium complex precursor, the functional group of the ligand, the gas atmosphere, temperature and holding time of the Joule heating process, etc.

[0006] The technical solution of the present invention is as follows: a sp&sp 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst, the preparation method comprises the following steps:

[0007] 1) Add 1,3,5-triynylbenzene and CuCl powder into a sample bottle;

[0008] 2) adding pyridine to 1) and shaking until the solid is dissolved;

[0009] 3) Place in a constant temperature water bath to react for a certain period of time;

[0010] 4) After the reaction is completed, soak and wash with pyridine, chloroform, ethanol and ultrapure water respectively;

[0011] 5) freeze-drying to obtain hydrogen-substituted graphyne aerogel;

[0012] 6) dissolving a certain amount of ruthenium complex in a certain amount of methanol;

[0013] 7) adding a certain amount of hydrogen-substituted graphyne aerogel to the solution of step 6) and soaking for a certain period of time;

[0014] 8) distilling the mixture obtained in step 7) under reduced pressure to remove methanol while allowing the ruthenium polypyridine complex to be uniformly adsorbed on the surface and pores of the hydrogen-substituted graphyne aerogel;

[0015] 9) The material obtained in step 8) is placed in a Joule heating apparatus, carbonized at a specific temperature for a certain period of time under an argon atmosphere, and cooled naturally to obtain the product Ru-N x / C.

[0016] One of the above sp&sp 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst, in step 1) and step 2), 1,3,5-triynylbenzene:CuCl:pyridine is 30mg:2-3mg:2mL.

[0017] One of the above sp&sp 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst, in step 3), the reaction temperature of the constant temperature water bath is 60°C, and the reaction time is 72h.

[0018] One of the above sp&sp 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst, in step 6), the ruthenium complex is dichlorobipyridylruthenium [Ru(bpy)2]Cl2 or terpyridylruthenium [Ru(bpy)3]Cl2.

[0019] One of the above sp&sp 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst, in step 6), the purity of [Ru(bpy)2]Cl2 is 98%, and the mixing ratio is [Ru(bpy)2]Cl2:methanol=40mg:15-20mL according to the solid-liquid ratio.

[0020] One of the above sp&sp 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst, in step 7), according to the mass ratio, [Ru(bpy)2]Cl2: hydrogen-substituted graphyne = 1:5, and the immersion time is 4-6h.

[0021] One of the above sp&sp 2Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst, in step 9), the carbonization temperature is 450-600°C, the holding time is 10-30 seconds, and the atmosphere is argon.

[0022] One of the above sp&sp 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x Application of C / C electrocatalysts in electrocatalytic nitrogen reduction.

[0023] The above application method is as follows: Ru-N supported by carbon cloth x / C electrocatalytic material is used as the working electrode, Ag / AgCl electrode is used as the reference electrode, carbon rod is used as the counter electrode, Nafion 117 is used as the proton exchange membrane, and nitrogen-saturated 0.1MNa2SO4 solution is used as the electrolyte, and electrocatalytic nitrogen production into ammonia is carried out in an H-type electrolytic cell.

[0024] For the above application, the preparation method of the working electrode is as follows: x / C is placed in a centrifuge tube, ultrapure water, ethanol and Nafion solution are added, ultrasonic dispersion is performed until the mixture is uniform, the dispersed liquid is dropped on the surface of the carbon cloth, and vacuum dried onto the working electrode.

[0025] The beneficial effects of the present invention are: providing a simple and efficient preparation method for high-performance Ru-based electrocatalysts (Ru-N x / C) technology, the catalyst can achieve efficient electrocatalytic nitrogen reduction to synthesize ammonia, and its ammonia synthesis efficiency is comparable to that of single-atom catalysts. The catalytic microenvironment around the Ru catalytic active center, such as the coordination number of Ru, the type and number of nearby heteroatoms, can be adjusted by regulating the synthesis conditions. Ru-N x The Ru-N / C catalyst activates nitrogen molecules through the π-backdonation effect, effectively inhibits the occurrence of hydrogen evolution side reactions, and has excellent selectivity and catalytic activity for electrocatalytic nitrogen reduction to synthesize ammonia. In addition, compared with graphene and other carbon materials, the catalyst carrier has abundant sp hybridized carbon and defect sites, which enhances the adsorption of nitrogen and further improves the Ru-N x / C electrocatalytic nitrogen reduction reaction activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is Ru-N x Scanning electron microscope (SEM) image of / C.

[0027] Figure 2 and Figure 3 It is Ru-N x Transmission electron microscopy (TEM) image of / C.

[0028] Figure 4 It is Ru-N x X-ray photoelectron spectroscopy (XPS) overall spectrum of / C.

[0029] Figure 5 It is Ru-N x X-ray photoelectron spectroscopy (XPS) high-resolution carbon spectrum of / C.

[0030] Figure 6 It is Ru-N x / C for the ammonia yield and Faraday efficiency diagram of the electrocatalytic nitrogen reduction reaction to produce ammonia. DETAILED DESCRIPTION

[0031] Example 1 A sp&sp 2 Hybrid carbon-based Ru-N with rich unsaturated coordination centers x / C composite catalyst

[0032] (I) Preparation method, Ru-N x The preparation of / C comprises the following steps:

[0033] 1) Add 30 mg of 1,3,5-triynylbenzene and 2-3 mg of CuCl powder into a sample bottle;

[0034] 2) Add 2 mL of pyridine to 1) and shake until the solid is dissolved;

[0035] 3) Place in a constant temperature water bath at 60°C for 72 hours;

[0036] 4) After the reaction is completed, soak and wash with pyridine, chloroform, ethanol, and ultrapure water in turn, each time for 24 hours;

[0037] 5) Freeze-drying to obtain hydrogen-substituted graphyne aerogel.

[0038] 6) Dissolve 40 mg [Ru(bpy)2]Cl2 in 20 mL methanol;

[0039] 7) adding 300 mg of self-made hydrogen-substituted graphyne aerogel to 6) and immersing for 4-6 h;

[0040] 8) removing methanol by reduced pressure distillation in 7) and allowing the ruthenium polypyridine complex to be uniformly adsorbed in the hydrogen-substituted graphyne aerogel;

[0041] 9) The material obtained in step 8) was placed in a Joule heating apparatus, carbonized at 450°C for 10 seconds under an argon atmosphere, and cooled naturally to obtain the product Ru-N x / C.

[0042] (II) Characterization

[0043] Figure 1 It is Ru-Nx Scanning electron microscope (SEM) image of / C.

[0044] Figure 2 and Figure 3 It is Ru-N x Transmission electron microscopy (TEM) image of / C. Figure 2 It shows that Ru-N x / C presents a two-dimensional nanosheet structure.

[0045] Figure 4 It is Ru-N x X-ray photoelectron spectroscopy (XPS) of / C. Figure 4 It shows that Ru-N x / C contains C, N, O, and Ru elements, of which Ru and N elements come from the [Ru(bpy)2]Cl2 precursor, C element mainly comes from the hydrogen-substituted graphyne aerogel precursor, and partly from the [Ru(bpy)2]Cl2 precursor, and the presence of O element is attributed to the adsorption of air and a small amount of oxygen-containing functional groups produced by the oxidation of acetylenes. No Cl element was detected in the composite, indicating that Cl was removed during the high-temperature carbonization process.

[0046] Figure 5 It is Ru-N x High-resolution X-ray photoelectron spectroscopy (XPS) of / C in the C1s and Ru 3d regions. Figure 5 It shows that in Ru-N x / There is sp in C 2 There are also sp hybridized C=C bonds and sp hybridized C≡C bonds. Among them, C=C comes from hydrogen replacing the carbon on the benzene ring of the graphene aerogel, and C≡C comes from hydrogen replacing the alkynyl group of the graphene aerogel. Ru elements can be divided into elemental Ru and oxidized ruthenium (RuO x ), RuO x The existence is due to the intermediate valence state of Ru between 0 and +3 after coordination, which proves that the coordination between Ru and N is successful. x The formation of structure.

[0047] Example 2Ru-N x Application of / C in electrocatalytic nitrogen reduction

[0048] (I) Preparation of working electrode

[0049] Take 5mgRu-N x / C powder, add 480μL ethanol, 500μL ultrapure water and 20μL 5wt% Nafion solution, and ultrasonically disperse for 30min until the mixture is uniform. Take 30μL of the dispersion and drop it evenly on the carbon cloth (1×1cm 2 ) and dried under vacuum at 60°C for 12 h for later use.

[0050] (II) Ammonia production performance test

[0051] Under ambient conditions, an H-type electrolytic cell was used as the reactor, and the anode and cathode were separated by a Nafion 117 proton exchange membrane. The electrolyte was 0.1M Na2SO4 solution, and the volume of the anode and cathode electrolyte was 70 mL. x / C is the working electrode, Ag / AgCl electrode is the reference electrode, and carbon rod is the counter electrode. During the experiment, nitrogen was first passed into the electrolyte at a flow rate of 20mL / min for 30min to ensure that the electrolyte was saturated with N2, and then the electrochemical test was carried out at different potentials for 2h while nitrogen was continuously passed. The ammonia content in the electrolyte was detected by indophenol blue spectrophotometry, and the results are shown in Figure 6 .

[0052] Figure 6 Ru-N x / C in 0.1MNa2SO4 solution, ammonia yield and Faraday efficiency at different potentials. Figure 6 As shown in Figure 2, the material has the best ammonia synthesis performance at -0.1 V (relative to reversible hydrogen electrode), and the best ammonia yield is 36.71 μg·h -1 mg -1 cat , and the Faraday efficiency is 33.49%. This ammonia yield is comparable to that of noble metal-based single-atom catalysts. The present invention provides a new idea for the design and construction of electrocatalytic nitrogen reduction ammonia synthesis catalyst.

Claims

1. A sp&sp 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst, characterized in that The preparation method comprises the following steps: 1) Add 1,3,5-triynylbenzene and CuCl powder into a sample bottle; 2) adding pyridine to 1) and shaking until the solid is dissolved; 3) Place in a constant temperature water bath to react for a certain period of time; 4) After the reaction is completed, soak and wash with pyridine, chloroform, ethanol and ultrapure water respectively; 5) freeze-drying to obtain hydrogen-substituted graphyne aerogel; 6) dissolving a certain amount of ruthenium complex in a certain amount of methanol; 7) adding a certain amount of hydrogen-substituted graphyne aerogel to the solution of step 6) and soaking for a certain period of time; 8) distilling the mixture obtained in step 7) under reduced pressure to remove methanol while allowing the ruthenium polypyridine complex to be uniformly adsorbed on the surface and pores of the hydrogen-substituted graphyne aerogel; 9) The material obtained in step 8) is placed in a Joule heating apparatus, carbonized at a specific temperature for a certain period of time under an argon atmosphere, and cooled naturally to obtain the product Ru-N x / C.

2. A sp&sp according to claim 1 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst, characterized in that: In step 1) and step 2), 1,3,5-triynylbenzene:CuCl:pyridine is 30 mg:2-3 mg:2 mL.

3. A sp&sp according to claim 1. 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst, characterized in that: In step 3), the reaction temperature of the constant temperature water bath is 60° C. and the reaction time is 72 h.

4. A sp&sp according to claim 1. 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst, characterized in that: In step 6), the ruthenium complex is ruthenium dichlorobispyridyl [Ru(bpy)2]Cl2 or ruthenium terpyridyl [Ru(bpy)3]Cl2.

5. A sp&sp according to claim 4 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst, Features: In step 6), the purity of [Ru(bpy)2]Cl2 is 98%, and the mixing ratio is [Ru(bpy)2]Cl2:methanol=40mg:15-20mL in terms of solid-liquid ratio.

6. A sp&sp according to claim 5 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst, characterized in that: In step 7), the mass ratio of [Ru(bpy)2]Cl2: hydrogen-substituted graphyne is 1:5, and the immersion time is 4-6 hours.

7. A sp&sp according to claim 1. 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x / C electrocatalyst, characterized in that: In step 9), the carbonization temperature is 450-600° C., the holding time is 10-30 seconds, and the atmosphere is argon.

8. The sp&sp according to claim 1 2 Hybrid carbon immobilized Ru-N with rich unsaturated coordination centers x Application of C / C electrocatalysts in electrocatalytic nitrogen reduction.

9. The use according to claim 8, characterized in that: The method is as follows: Ru-N supported by carbon cloth x / C electrocatalytic material is used as the working electrode, Ag / AgCl electrode is used as the reference electrode, carbon rod is used as the counter electrode, Nafion 117 is used as the proton exchange membrane, and nitrogen-saturated 0.1MNa2SO4 solution is used as the electrolyte, and electrocatalytic nitrogen production into ammonia is carried out in an H-type electrolytic cell.

10. The use according to claim 9, characterized in that: The preparation method of the working electrode is as follows: take Ru-N x / C is placed in a centrifuge tube, ultrapure water, ethanol and Nafion solution are added, ultrasonic dispersion is performed until the mixture is uniform, the dispersed liquid is dropped on the surface of the carbon cloth, and vacuum dried onto the working electrode.

Citation Information

Patent Citations

  • Preparation method for carbon-supported ultrafine ruthenium nanocrystalline composite material

    CN109225211A

  • Preparation method of Ru-based catalyst with controllable particle size and application of Ru-based catalyst in'renewable energy electrolytic hydrogen production-ammonia synthesis'

    CN114182293A

  • Method for preparing ruthenium-fluorine / phosphide catalyst by solid phase method and application of ruthenium-fluorine / phosphide catalyst

    CN118835272A